Monitoring Kelistrikan Tree Wind Turbine Berbasis Internet of Things - Paisal; Taufik , Akhmad; Yansi Parorengan; Al Azhali SR , Arham (Politeknik Negeri Ujung Pandang, 2026)
Abstract: The Tree Wind Turbine is an innovative renewable energy solution designed in the shape of a tree, with small turbines acting as “leaves” that capture wind from various directions. This design is well-suited for urban environments due to its aesthetic appearance and eco-friendly nature. However, the system requires real-time monitoring of current and voltage from each turbine to ensure optimal efficiency and to detect potential issues early.This research aims to design an Internet of Things (IoT)-based monitoring system to track current, voltage, and wind speed on each turbine in real time. The system uses an ESP32 microcontroller, equipped with ACS712 current sensors, 0–25V voltage sensors, and ADS1115 modules for accurate readings. The collected data is transmitted to an online database and displayed in graphical form through a web dashboard.Testing results show that the system successfully monitors electrical data such as voltage, current, and wind speed accurately. The data is displayed in real time and remains stable, enabling clear differentiation between the performance of turbines with 3, 4, and 5 blades. This system effectively supports efficient wind energy utilization and serves as a practical IoT-based monitoring solution for urban settings. Keywords: esp32; sensor; turbine; savonius; monitoring; wind speed